(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
In philosophy of religion, language serves as a medium of expression of religious meaning, as it is descriptive and possesses true-false faculty in mysticism. In philosophy of language, religion is one of the backgrounds or contexts in the production of religious meaning and interpretation. This shows the symbiotism of language and religion within the philosophy of religion and philosophy of language. This article discusses the position of language and religion within the two philosophies from the viewpoints of two 20th century British analytic philosophers, namely Hick and Ayer, with the objectives of: (1) identifying the meeting point of language and religion in philosophy; (2) detailing the boundaries of language and religion according to the division of linguistic philosophy and religious philosophy, and; (3) parsing the Malay linguistic response to the products of British analytic philosophical thought. The focus of analysis is metaphysics. The metaphysical arguments were analysed based on the function of language in the philosophy of religion that Hick (1990) highlighted in Philosophy of Religion, as well as the religious background in the philosophy of language that Ayer (1936) put forward in Language, Truth and Logic.